An efficient implementation of revocable functionality in authentication protocol for wireless body area network. Issue 2 (17th February 2021) - Singh, Rashmi; Joshi, Ashish; Mohapatra, A. K.; Jha, V. N.
Abstract: This paper provides the list of all the features that should be required in designing the authentication protocol for wireless body area network and enhances the implementation of revocation functionality given by Xiong and Qin by executing the same in different data structures. The comparative results show that the instead of using complete binary tree in executing revocation functionality, the use of heap or AVL will provide better results by making the performance of protocol less expensive in terms of computation as well as memory.